Stoichiometry of An(III)-DMDOHEMA complexes formed during solvent extraction - Weßling, Patrik; Panak, Petra (Dalton transactions, 2018)
N,N′-Dimethyl,N,N′-dioctylhexylethoxymalonamide (DMDOHEMA) is used to separate An(III) and Ln(III) from fission products in several liquid-liquid extraction processes that aim at recycling actinides. The stoichiometry of the extracted complexes is important for a complete understanding of the processes. The presented work focuses on the complexation of Cm(III) with DMDOHEMA studied by TRLFS in mono- and biphasic (solvent extraction) systems. The formation of [Cm(DMDOHEMA)n]3+ (n = 1-3) in 1-octanol containing 1.7 mol L−1 of water with log β′1 = 2.6 ± 0.3, log β′2 = 4.0 ± 0.5, log β′3 = 4.3 ± 0.5 was confirmed. In addition, fluorescence lifetime measurements indicated the formation of a 1 : 4 complex. Furthermore, solvent extraction experiments were performed, varying the proton and nitrate concentrations. TRLFS measurements of organic phases confirmed the existence of two species, [Cm(DMDOHEMA)3(NO3)(H2O)1-2]2+ (dominant at high proton and nitrate concentrations) and [Cm(DMDOHEMA)4(H2O)]3+ (dominant at low proton and nitrate concentrations). To support the proposed stoichiometries, vibronic side-band spectroscopy (VSBS) was employed, allowing the observation of vibrations of functional groups coordinated to the probed metal ion. Clear differences between the vibronic side bands of the 1 : 3 and 1 : 4 complex in the range of 900-1300 cm−1 were observed. Vibrational spectra calculated by DFT complimented the experimental data and confirmed the proposed stoichiometries. They revealed a monodentate coordination mode of the nitrate and two water molecules in the 1 : 3 complex.
Gesehen am 12.03.2020